LOCALISING KNOWLEDGE TO DEVELOP THE NATION - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG,22 February 2017 – Efforts to promote knowledge to communities, which would lead to a highly civilised society with a strong knowledge base and having exemplary achievements, would be realised when such knowledge could be interpreted into outcomes and improvements on such knowledge could be well understood and implemented.